Keeping found things found: Challenges and usefulness of personal information management among academicians. Issue 12 (17th October 2018) - Warraich, Nosheen Fatima; Ali, Irfan; Yasmeen, Shazia
Abstract : Purpose: This study aims to investigate the usefulness and challenges of personal digital information management (PDIM) as perceived by engineering faculty members. Design/methodology/approach: Quantitative research strategy based on survey design was used to collect data through structured questionnaire. Simple random sampling technique was applied to obtain a representative sample from faculty members of University of Engineering and Technology, Lahore. Findings: Findings indicate that faculty members understand the usefulness of PDIM practices for their teaching and learning. They opined that these practices improve their performance along with effective utilization of resources. PDIM practices save their time, energy and money. Nevertheless, they have to face challenges in managing their personal information in digital format including technology obsolescence, bulk of incoming emails, prediction of future value of information, information fragmentation and memory load in remembering the location of information. It is also noted that PDIM practices are equally useful for both male and female faculty members. However, female faculty members have to face more PDIM challenges than male faculty members. Practical implications: Overall, findings of the study reveal that there are benefits of PDIM and it is useful for faculty members with certain challenges. This study identified five major challenges. All these challenges were from technological and cognitive psychology domain. It is noted that assessing future value of information plays important role in overall process of PDIM. Originality/value: The present study would be valuable addition in literature and it would be helpful in devising information literacy instructions programs in academic libraries. This study would also helpful for improving quality services for teaching as required by Pakistan Engineering Council. Findings of this study would helpful for system engineers, software developers and system librarians in designing and developing personal information management systems in Pakistan.